Chemical composition and biological activities of essential oils and extract of Eucalyptus citriodora Hook - Bihter Şahin; Mehmet Öztürk; Cansel Cakır; Yusuf Sıcak (International Journal of Secondary Metabolite)
In this study, the leaves of Eucalyptus citriodora Hook (Lemon-Scented Eucalyptus) were harvested and collected from Üzümlü neighborhood of Fethiye district of Muğla in 2021. Chemical content analysis of steam distillation and hydrodistillation of essential oils were determined by GC-MS, while phenolic content of methanol extract was determined by HPLC-DAD. Antioxidant activities of essential oils and methanol extracts were determined by DPPH radical removal, ABTS cation removal, β-carotene linoleic acid, and CUPRAC activity methods; Anticholinesterase activity against AChE and BChE enzymes was determined by Ellman method; and tyrosinase inhibition associated with melanin hyperpigmentation, α-amylase inhibition, and α-glucosidase inhibition activities associated with diabetes were determined as an in vitro. The bioactivities and chemical contents of E. citriodora species, a great value of, Türkiye, were determined, bringing new natural products to organic chemistry. As a result of the study, new bioactive extracts would be obtained and thus, they can effectively reveal the potential of new business opportunities. Since methanol extract is effective against incurable diseases such as Alzheimer's and diabetes, it will also be possible to develop therapeutics of such diseases by investigating the advanced chemistry and in vivo activities of the extracts with new projects.